Religion, modernity and homosexual ordination in a liberal protestant denomination - Johnson, Fredrick Boyd (My University, 1993)
The United Church of Canada's General Council determined that all members could be considered for ordained ministry regardless of sexual orientation in 1988. The membership was not unanimous in this matter. This research tests the hypothesis that the response to homosexual ordination will reflect social differences which are related to modernity. The research involved a survey questionnaire completed by members/adherents of a United Church of Canada congregation in Thunder Bay, Ontario.
Keywords: United Church of Canada; United Church of Canada Clergy; Homosexuality Religious aspects United Church of Canada